Modeling Adiabatic Boiling in the Biliran Geothermal Wells Using CHIM-XPT (2016) - Mendoza, John Paul A.; Balangue-Tarrieta, Maria Ines; Reed, Mark H. (2019)
Boiling is a common process in geothermal wells where the primary water quickly ascends to the surface and liquid water is converted to steam due to depressurization and cools downs (i.e., no heat exchange with surrounding rocks). An assumption in the present study is that there is no heat exchange between wall rock and boiling water; thus, the process is isenthalpic. This study presents the results of changes in the chemical composition of fluid from a geothermal system as it ascends to the surface together with the description of minerals precipitating out of the solution at certain temperature conditions. The results of the study will contribute significantly to the assessment of scaling potentials in a geothermal field. Using FORTRAN Programs SOLVEQ and CHIM-XPT, adiabatic boiling was simulated for the normal enthalpy wells of Biliran geothermal field. Results of theoretical geothermometry for the wells are consistent with the reported chemical geothermometers. Aside from a steam phase dominated by water vapor and CO2, Well BN-1 formed chlorite, calcite (up to 170 °C) and talc in the initial boiling model. Well BN-2 precipitated mostly talc and calcite almost all throughout its ascent. The occurrence of calcite calculated from the model is consistent with the abundance of calcite scales and veins in BN-1 while BN-2 is dominated by aragonite. Minor differences in the mineralogy of the wells is mainly due to the significant difference in the fluid and gas chemistry amongst wells in the field. The partitioning of CO2 into a gas phase drives the increase in pH for both wells. Both the formation of the gas phase and the fractionated minerals reflect changes occurring in the total concentration of the aqueous phase wherein species fractionated into the gas or solid phase decrease in the total aqueous concentration.
Keywords: Geothermal resources; Hydrothermal synthesis